Penerapan Nilai-Nilai Pendidikan Karakter Hindu di SD Sathya Sai Banjar Bantas Desa Peguyangan Kangin Kecamatan Denpasar Utara: Penelitian - Ninick Sumahendri; Suwandana, Adi; Gusti Ayu Alet Irmawati, Ni; Gusti Bagus Punama, I (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The objective of this research is to comprehend the form of application of character education values, to determine the implications of character education, and to identify the efforts made to overcome problems in implementing Hindu character education at SD Sathya Sai Banjar Bantas, Peguyangan Kangin Village, North Denpasar District. The data collection method was dissected using Value Theory, Motivation Theory, and Character Education Theory. Data were analyzed using qualitative descriptive analysis. The research findings indicate: (1) The values found include Religious Value, Discipline Value, Independent Value, Tolerance Value, Reading Enthusiasm Value, and Environmental Care Value. (2) The implications of Hindu character education at SD Sathya Sai Banjar Bantas, Peguyangan Kangin Village, North Denpasar District, are: 1) Enhancing students' religiousness by consistently performing prayers and silent sitting (light meditation). 2) Improving students' disciplinary behavior at school. 3) Boosting independent attitude in completing school assignments. (3) The efforts made to overcome problems in implementing Hindu character education at SD Sathya Sai Banjar Bantas, Peguyangan Kangin Village, North Denpasar District, are increasing students' knowledge, creating enjoyable lessons for students, improving student relationships, enhancing teachers' teaching strategies, addressing teacher administration issues, and addressing the family environment.